PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA CV. PUTRI LINTANG SAKTI BANDAR LAMPUNG - Kusminaini Armin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
ABSTRACTÃ‚Â The formulation of the problem in this research is How does working capital on the profitability of the CV. Putri Lintang Sakti Bandar Lampung. The purpose of this study to determine the effect of working capital on the profitability of the CV. Putri Lintang SaktiBandarLampung. This research is a quantitative study. Religious studies done on CV. Lintang Sakti Bandar Lampung. The variables used are working capital (X) and profitability (Y). Data used secondary data thatÃ‚Â financial statements. CV Lintang Sakti Ã‚Â in 2009 - 2011. analysis is qualitative analyzes of data analysis techniques using liquidity ratios, profitability. To analyze the effect of working capital on profitability using simple regression analysis and t test. The results of the regression analysis shows that there is an influence waged between working capital profitability. It can be seen from the simple regression equation and t test. Values obtained by t test t = 3.385, TTable = 12.70 then, Ho is accepted, it means there is an influence but not more significan betweenÃ‚Â working capital (X) and profitability (Y) in the CV. Lintang Sakti Bandar Lampung Keywords: Effect of working capital on profitabilityÃ‚Â